2009
DOI: 10.1002/agr.20200
|View full text |Cite
|
Sign up to set email alerts
|

Members' perception of their participation in the governance of cooperatives: the key to trust and commitment in agricultural cooperatives

Abstract: This study explores to which extent the members' assessment of their cooperatives' degree of success are related to various member attributes, with special reference to the members' perception of their participation in the governance of the cooperatives. Three categories of member attributes are identified: Satisfaction with the profitability of farm operations, Age, and Experience from board work. The cooperatives' degree of success is measured as members' commitment towards cooperatives, and members' trust i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
168
0
38

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(216 citation statements)
references
References 15 publications
10
168
0
38
Order By: Relevance
“…There are variations in the Ethiopia SPCs with regard to members' skills and capabilities in seed production, seed business, and commitment, which is reflected in their performance . The cooperatives' degree of success is measured as members' commitment toward cooperatives, and members' trust in the board of directors (Österberg and Nilsson 2009). There are some members that are opportunistic in getting higher prices via other market outlets even if they have an agreement with their SPC.…”
Section: Challenges For Seed Producer Cooperativesmentioning
confidence: 99%
“…There are variations in the Ethiopia SPCs with regard to members' skills and capabilities in seed production, seed business, and commitment, which is reflected in their performance . The cooperatives' degree of success is measured as members' commitment toward cooperatives, and members' trust in the board of directors (Österberg and Nilsson 2009). There are some members that are opportunistic in getting higher prices via other market outlets even if they have an agreement with their SPC.…”
Section: Challenges For Seed Producer Cooperativesmentioning
confidence: 99%
“…Medium sized farmers' attitudes towards the cooperative have been found to be positive, however larger sized farmers are more critical. In other studies, no such correlation has been found (Österberg & Nilsson, 2009). In agricultural cooperatives, the land size of the shareholder, the duration in cooperative shareholder, the time in farming, and the educational levels revealed the existence of a relationship between performance and satisfaction of the shareholders that has been investigated (Hansen et al, 2002;Bakucs, Ferto, & Szabo, 2007).…”
Section: Demographic Of Shareholders (Members' Characteristics)mentioning
confidence: 68%
“…The horizontal expansion is likely to create distances between members and between members and the leadership. Because of weakened social ties member involvement shrinks (Nilsson et al, , 2012Österberg and Nilsson 2009). …”
Section: The Development Of Farmer-controlled Businessesmentioning
confidence: 99%
“…The findings from these studies are quite diverse but there is a common feature, namely that there are systematic differences between farmers supplying to co-operatives and farmers supplying to IOFs. Farmers tend to appreciate the social links within the membership body and the fact that the co-operative constitutes a reliable trading partner (Bhuyan, 2007;Gray and Kraenzle, 1998;Österberg and Nilsson, 2009). However, it is important that they can trust their co-operatives and feel that they are being properly treated (Borgen, 2001;Hansen et al, 2002;Nilsson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%